PENGETAHUAN DAN SIKAP MASYARAKAT TERKAIT KUSTA DAN PERLAKUAN DISKRIMINASI PADA PENDERITA KUSTA : STUDI KASUS DI KOTA TARAKAN - Sulidah Sulidah (IJNP (Indonesian Journal of Nursing Practices), 2015)
Background: Indonesia is one of the world’s biggest contributor to leprosy. A long and convoluted chain of transmission is complicating factor in the leprosy control program. Physical disabilities as an impact of leprosy causes excessive fear in the community. Negative stigma and leprophobia resulted in lepers often being subjected to discrimination. The low level of public knowledge about leprosy lead to negative attitude of society is thought to be a discrimination trigger.Objective: The study aimed to identify the level of public knowledge about leprosy, public attitudes to leprosy patients, and to analyze the relationship between knowledge and attitudes towards discrimination. Methods: This is a case study conducted in the Tarakan city utilising cross sectional design. A sample size of 227 respondents aged from 18-60 years were taken by purposive sampling technique. The research instrument in the form of a structured questionnaire with a Cronbach’s Alpha of 0.81. Analysis of the relationship between knowledge and attitudes towards discriminated on leprosy patients were tested using the Mann-Whitney.Results: this study identifi ed the level of public knowledge about leprosy is still low; negative attitudes; and the tendency of discrimination in patients with leprosy. Analysis of the relationship between variables which produces a signifi cance level of p = 0.000.Conclussion: there is a signifi cant correlation between public knowledge about leprocy and public attitudes to leprosy patients against discrimination in patients with leprosy.Keywords: Knowledge, Attitude, Leprosy, Discrimination.